Evaluasi Pengelolaan Strategi dan Kerangka Kerja Teknologi Informasi pada Dinas Komunikasi dan Informatika Kota Malang Menggunakan COBIT 5 - Hetti Marthaningrum; Admaja Dwi Herlambang; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang continues to initiate a digital-based government and budgeting system to achieve Malang Smart City in 2020. However, based on the results of the 2018 SPBE evaluation, the results have not been maximized. This is due to the lack of policies that form the basis or legal umbrella in the implementation of SPBE. In addition, the lack of utilization of IT governance in the administration of local government also results in e-government effectiveness. For this reason Dinas Kominfo Kota Malang needs an effective IT governance reference. The purpose of this research is to evaluate the management of strategies and IT frameworks using COBIT 5. The results of the evaluation are used as a basis for recommendations for improvement to support the improvement of SPBE evaluation results the next year to Malang Smart City 2020. Based on the measurement results of capability level in the Manage the process The IT Management Framework (APO01) and Manage Strategy (APO02) both reach level 1. Furthermore, an analysis of the gap between capability levels and targeted levels is carried out as a basis for preparing recommendations. Each recommendation given will be mapped into a road map that shows the planned program or activity along with the achievement targets for each process that is evaluated. In addition, recommendations were made based on ITIL V3 2011 guidelines related to The Seven-Step Improvement Process and Strategy Management for IT Services.